Single-step Preparation of Nano-homogeneous NiO/YSZ Composite Anode for Solid Oxide Fuel Cells - Song, Jung-Hoon; Park, Mi Young; Park, HyeWon; Lim, Hyung-Tae (Nano-Micro Letters, 2013)
Homogeneous co-precipitation and hydrothermal treatment were used to prepare nano- and highly dispersed NiO/YSZ (yttria-stabilized zirconia) composite powders. Composite powders of size less than 100 nm were successfully prepared. This process did not require separate sintering of the YSZ and NiO to be used as the raw materials for solid oxide fuel cells. The performance of a cell fabricated using the new powders (max. power density ∼0.87 W/cm2) was higher than that of a cell fabricated using conventional powders (max. power density ∼0.73 W/cm2). Co-precipitation and hydrothermal treatment proved to be very effective processes for reducing cell production costs as well as improving cell performance.